Evidence Brief: Using Financial Incentives to Achieve Health-system Goals in Ontario - Lavis, JN; Wilson, MG; Grimshaw, J; Hurley, J (My University, 2015)
An assessment of what is known about problems related to health-system, options for addressing these problems, and key implementation considerations. The evidence brief was an input to a stakeholder dialogue on the topic of using financial incentives to achieve health-system goals in Ontario.
Keywords: financial; incentives; health system; Ontario